The Assessment of Knowledge about Tourette’s Syndrome among Medical Students and Primary Physicians in Riyadh, Saudi Arabia: A Cross-Sectional Study - Anas A. Alalwan; Mohammad A. Alkhamis; Ahmad M. Samman; Enan H. M. Alsharif; Omar E. M. Tarabzoni; Ismail A. Khatri (Neurology Research International)
Background. Tourette’s syndrome (TS), a chronic, often disabling neuropsychiatric disorder characterized by motor and vocal tics, is frequently misdiagnosed, or patients are delayed in diagnosis. There is severe deficiency of research about Tourette’s syndrome (TS) in the Middle East region. Objectives. To evaluate the knowledge and attitude of medical students and primary care physicians (PCPs) about TS and tic disorders. Methods. IRB approved, cross-sectional study. A total of 316 medical students of King Saud bin Abdulaziz University and 59 primary care physicians of Riyadh participated. Convenient, cluster sampling was used. A validated, self-administered questionnaire was used. Sum of all knowledge questions was calculated. Data were analyzed using SPSS software. Results. Survey was completed by 375 students and physicians, of whom 253 (67.5%) were men. Mean general knowledge score was 61.5 (±12.04) out of 100. Majority (66.1%) knew the diagnostic criteria for TS; only 46.1% considered antipsychotics as effective treatment. Only 25.1% had ever heard of habit reversal; 70% wanted to learn more. Only 10% of physicians had treated a patient with TS. There was no difference in knowledge between men and women (p=0.776). Board-certified physicians had a higher knowledge score (p<0.05). Family physicians demonstrated higher level of knowledge compared to other physicians (p<0.05). There was no difference between knowledge of students of different years (p=0.859) or between students and physicians (p=0.569). Conclusion. There was alarming lack of knowledge about Tourette syndrome at various level of medical training and practice including students and physicians. Those who achieved board certification and practiced as family physicians fared better in knowledge about Tourette’s syndrome.